2018
DOI: 10.1038/s41467-018-03013-5
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific phosphorylation of TRANSPARENT TESTA GLABRA1 mediates carbon partitioning in Arabidopsis seeds

Abstract: Seed development is dependent on nutrients, such as a source of carbon, supplied by the parent plant. It remains largely unknown how these nutrients are distributed to zygotic and maternal tissues to coordinate storage of reserve compounds and development of protective tissues like seed coat. Here we show that phosphorylation of TRANSPARENT TESTA GLABRA1 (TTG1) is regulated by SHAGGY-like kinases 11/12 (SK11/12) and that this mediates carbon flow to fatty acid synthesis and seed coat traits in Arabidopsis seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 50 publications
0
68
0
Order By: Relevance
“…TRANSPARENT TESTA 8 (TT8), for instance, can directly inhibit the transcription of LEC1, LEC2, and FUS3 (Chen et al, 2014). This basic helix-loop-helix (bHLH) TF can form a ternary complex with an R2R3-MYB factor TT2 and a WD40 repeat factor TRANSPARENT TESTA GLABRA 1 (TTG1) to monitor carbon partitioning among metabolic pathways that share the same source, including seed oil, mucilage and flavonoid synthesis (Li et al, 2018). Interestingly, there is a TT2-FUS3-TTG1 cascade linked via direct gene suppression (Wang et al, 2014;Chen et al, 2015).…”
Section: Transcriptional Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…TRANSPARENT TESTA 8 (TT8), for instance, can directly inhibit the transcription of LEC1, LEC2, and FUS3 (Chen et al, 2014). This basic helix-loop-helix (bHLH) TF can form a ternary complex with an R2R3-MYB factor TT2 and a WD40 repeat factor TRANSPARENT TESTA GLABRA 1 (TTG1) to monitor carbon partitioning among metabolic pathways that share the same source, including seed oil, mucilage and flavonoid synthesis (Li et al, 2018). Interestingly, there is a TT2-FUS3-TTG1 cascade linked via direct gene suppression (Wang et al, 2014;Chen et al, 2015).…”
Section: Transcriptional Factorsmentioning
confidence: 99%
“…The repressor TTG1 is regulated by shaggy-like kinases 11/12 (SK11/12) that belongs to the glycogen synthase kinase-3 (GSK3) family (Li et al, 2018). Of note, SK11 (or ASKα) can be induced by salt stress (Dal Santo et al, 2012).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The bes1 bzr1 loss-of-function mutants and bes1-D bzr1-D gain-of-function mutants were as reported previously 34 . pSK11:GUS and pSK12:GUS lines were as reported previously 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed that the vascular cells express SKII subgroup genes BIN2 and BIN2-LIKE2 (BIL2) 24 . In addition, expression of SKI subgroup genes pSK11:GUS and pSK12:GUS 25 was found in the vasculature including the phloem tissue (Fig. 4f).…”
Section: Genetic Manipulation Of Gsk3 Activity Alters the In Vivo Se/mentioning
confidence: 97%